BUSINESS DEVELOPMENT STRATEGY : QUANTITATIVE STRATEGIC PLANNING MATRIX (QSPM) PERSPECTIVES - Dianka Wahyuningtias; Meiryani Meiryani (Ultima Management : Jurnal Ilmu Manajemen, 2022)
Abstract- King's Promotion Indonesia is a company engaged in international bag production services. This study uses a quantitative strategic planning matrix method by evaluating alternative options objectively, determining attractiveness, then deciding the best strategy. The purpose of this study is to analyze internal and external conditions of the company and formulate a business strategy in order to gain a competitive advantage for the company. The research method used in this research is descriptive qualitative method with the type of case study research. Data collection techniques using interviews, surveys and questionnaires conducted on related parties within the company. The data that has been obtained were analyzed using the grand strategy matrix and QSPM. The result of the grand strategy shows that the alternatives that can be applied by the company are market penetration and product development strategies. The results of this study provide alternative strategies, namely improving product quality, developing product variants and designs, and making market pricing strategies in the face of competition. The results of this study show consistency of resource-based theory which states that companies that can maintain its competitive advantage has the ability to create added value for stakeholders. Keywords: Market Development, Product Development, Strategy Management, QSPM Matrix